2020
DOI: 10.3126/ojn.v10i1.30996
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Pattern of Canine Impaction and Its Associated Anomalies among Orthodontic Patients Attending Tertiary Care Dental Hospital in Kathmandu

Abstract: Introduction: Permanent canines are considered as the cornerstone of mouth. Canines are important for esthetics and function as they are located in the anterior segment of the mouth and help in tearing of food. An impacted tooth is that tooth that cannot or will not erupt into its normal functional occlusion due to some circumstances. Those impacted tooth are considered pathologic as they might lead to various problems like resorption of roots of adjacent teeth, cystic formation, and infection with partial eru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…An investigation of 580 Bangladeshi radiographic records found that only 7 (1.2%) radiographs had impacted maxillary canines. 19 Piya et al 20 estimated that for all the 550 patients treated in Kathmandu's tertiary care dental hospital, the canine impaction prevalence was 5.6%. Volume 59 -June 2021 ISSN: 1110.435X Melha et al 21 assessed canine tooth impaction among the population of Riyadh in Saudi Arabia, analysed 2157 patients' panoramic radiographs and found canine impaction in 79 patients (3.65%).…”
Section: Discussionmentioning
confidence: 99%
“…An investigation of 580 Bangladeshi radiographic records found that only 7 (1.2%) radiographs had impacted maxillary canines. 19 Piya et al 20 estimated that for all the 550 patients treated in Kathmandu's tertiary care dental hospital, the canine impaction prevalence was 5.6%. Volume 59 -June 2021 ISSN: 1110.435X Melha et al 21 assessed canine tooth impaction among the population of Riyadh in Saudi Arabia, analysed 2157 patients' panoramic radiographs and found canine impaction in 79 patients (3.65%).…”
Section: Discussionmentioning
confidence: 99%
“…Following that, it migrates downwards and forward to lie mesial and buccal to the apex of the deciduous canine, then progresses downwards along the distal half of the upper lateral incisor's root. 20 According to Piya et al, 6 before the crown of the tooth, is calcified, the canine remains high in the maxilla, often above the root of the lateral incisor. It subsequently erupts over the distal surface of the lateral incisor, closing any physiological diastema that may exist as the canine erupts into position.…”
Section: Canine Impaction Development Etiology and Prevalencementioning
confidence: 99%
“…This is referred to as the ugly duckling stage. 6 Maxillary canines often arise between 11 and 12 years. 12 The mandibular canines begin to calcify at the age of four months, and the enamel of the crown is fully grown by the age of seven years.…”
Section: Canine Impaction Development Etiology and Prevalencementioning
confidence: 99%
See 2 more Smart Citations